Natural and Synthetic Phosphodiesterase Inhibitors in 2023: an Update on the Impact on Neurological and Psychiatric Conditions - Ribaudo, Giovanni; Gianoncelli, Alessandra (Mini Reviews in Medicinal Chemistry, 2024)
This Perspective provides an updated overview on the involvement of phosphodiesterase (PDE) isoforms and of the corresponding inhibitors in neurological disorders, including dementia, Parkinson’s disease, multiple sclerosis, neuropsychiatric conditions and cerebral ischemia. Particular attention has been dedicated to natural and semi-synthetic compounds. Translation into the clinic of preclinical results, toxicity profile and bioavailability represent the challenging aspects in the development of PDE inhibitors. With the aim of providing the latest updates to the reader, the 2023 contributions in the field were considered for the preparation of this Perspective.
Keywords: schizophrenia